The effects of climate change on gender roles among agro-pastoral farmers in Nabilatuk district, Karamoja subregion, North Eastern Uganda - Ayub, Mukisa; Muhanguzi, Florence Kyoheirwe; Boonabaana, Brenda (Frontiers in Human Dynamics, 2023)
This study examines the effects of climate change on gender roles among agro-pastoral farmers in Nabilatuk District, Karamoja subregion, in North Eastern Uganda. Data were collected from 10 focus group discussions, 10 key informant interviews, and observation. Atlas Ti 7.5.18. Software was used to analyze data. Findings indicate that climate change has disrupted traditional gender roles among men and women in Karamoja. Because of this, men have been forced to shift from pastoralism to crop farming. Additionally, some men have taken on reproductive roles which were formerly female dominated. Women, on the other hand have taken on petty trade in trading centers, which was formerly only a men's pursuit. With this has come an increased workload for women, leaving them even more vulnerable. This shift brings to question the notion of stability of gender roles, and how this affects the agricultural productivity of both men and women. Conclusively, there is a need for the adaptation of gender sensitive strategies which can reduce the work burden of women.